Hematocrit as assessment criterion of erythrocyte response to the change in the medium osmolality - Сєміонова, К. А.; Ніпот, О. Є.; Орлова, Н. В.; Шпакова, Н. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The change in hematocrit of mammals (human, horse, bull, rabbit, rat), depending on NaCl concentration in the medium at 0 and 37ºC has been comparatively studied. Non-linear change in hematocrit with increasing concentrations of NaCl has been demonstrated. Herewith the minimums of hematocrit dependencies have been observed in the media: 0.4 mol/l NaCl – for human and horse erythrocytes, 0.3–0.4 mol/l NaCl – for rat’s ones, 0.4–0.6 mol/l NaCl – for rabbit’s both at 37 and at 0ºC. Bovine cells unlike the erythrocytes of other mammals studied have shown a minimal hematocrit value at higher NaCl concentrations – 1.0 mol/l at 37ºC only.